Concrete containing modified activated stone powder and preparation method thereof
By modifying granite stone powder and modified limestone powder, combined with crosslinked polyurethane resin, the problem that stone powder in the prior art cannot improve the later strength and freeze-thaw resistance in concrete is solved, and the preparation of high-performance concrete is achieved, with excellent strength and freeze-thaw resistance, while reducing costs.
Patent Information
- Application Number
- CN202510315324.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-18
AI Technical Summary
In the prior art, stone powder is an inert component in concrete and cannot effectively improve the later strength and freeze-thaw resistance of concrete, and the high content of stone powder will affect the performance of concrete.
By modifying granite stone powder and modified limestone powder, combined with crosslinked polyurethane resin, the hydration activity and coordination effect of the stone powder are improved to form high-performance concrete. Modified granite stone powder is used to use a silane coupling agent, and the modified limestone powder is modified by calcination and aluminate coupling agent, and the cross-linked polyurethane resin is used to enhance the interweaving of stone powder and hydration products.
Concrete with high stone powder content has excellent initial and late strength, significantly improved freeze-thaw resistance, and maintained good flow, reducing the use of fly ash and slag, and reducing costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to concrete containing modified activated fossil powder and a preparation method thereof. Background Art
[0002] As a major building material, concrete is widely used, which places great demands on the demand for concrete. Fly ash and slag are known to be the main components of concrete admixtures, but with the rapid growth of concrete usage, the prices of fly ash and slag are rising. It has been reported in the literature that stone powder can be used as an admixture in the preparation of concrete to promote cement hydration and improve concrete performance. Stone powder can fill the gaps between concrete aggregates, increase the density of concrete, and thus increase strength. Stone powder has a wide range of sources and is cheap and easy to obtain. If it can be used on a large scale in concrete, it can reduce the amount of cement used and reduce costs. However, the use of stone powder in concrete has not yet been widely used. Stone powder is generally inert and cannot react with cement and other base materials to form gel. It is an inert filler in concrete. At present, concrete mixed with stone powder is mainly used in low-strength grade concrete. This is because stone powder directly added to concrete has no effect on the later strength, and even has an adverse effect. In addition, the use of stone powder will also reduce the time-loss performance of concrete slump.
[0003] CN103524062A discloses a modified limestone powder for making concrete, which is prepared from the following raw materials in parts by weight: 80-90 parts of limestone, 0.5-0.8 parts of isobutyl methacrylate, 1-2 parts of slaked lime, 2-4 parts of polypropylene fiber, 1-2 parts of alum, 0.2-0.4 parts of calcium formate, 1.2-1.5 parts of silane coupling agent KH550, 5-8 parts of fly ash, 0.6-0.8 parts of dioctyl maleate, 1-2 parts of styrene-butadiene latex, and 15-18 parts of modified jade powder; the preparation method of the modified jade powder is as follows: 30-40 parts of 1. 5-8 parts of jade, 5-8 parts of glass powder, and 3-5 parts of starch are mixed and flashed in a flash kiln at 800-900°C for 4-6 seconds, taken out, mixed with 3-5 parts of aluminum oxide and 2-3 parts of silicon carbide, and ground in appropriate amount of water, and 10-12% hydrochloric acid solution is added to adjust the pH to 5-6, and the slurry is ground to 600-800 mesh, and then sodium hydroxide solution is added to adjust to neutral, dried, and 0.4-0.6 parts of sodium silicate and 0.7-0.9 parts of chlorinated paraffin are added to the powder obtained after grinding, and mixed evenly, and then ground into nano powder. This patent uses jade as raw material, which is expensive; and it needs to go through flash burning, pickling, high-speed kneading and other steps, which is not suitable for large-scale industrial production.
[0004] CN107986657A discloses an active stone powder for concrete and a preparation method thereof. The active stone powder is prepared from the following raw materials in parts by weight: 100 parts of ordinary stone powder and 5-25 parts of an active modifier; the active modifier is at least one of active modifier A, active modifier B and active modifier C; the active modifier A is prepared by the following method: dispersing ethyl orthosilicate in an ethanol-water-ammonia solution at a mass ratio of 1-2:2-12, stirring until the solution changes from colorless and transparent to turbid and a large amount of floccules appear; the active modifier B is prepared by the following method: dispersing sodium silicate in water at a mass ratio of 1-2:3-5, stirring until the solid is completely dissolved; the active modifier C is prepared by the following method: dissolving silica sol in water at a mass ratio of 1-3:0-6. By modifying the stone powder, the activity index of the modified stone powder can reach the standard of Class II fly ash.
[0005] The stone powder content of concrete provided in the prior art cannot be too high, otherwise it will affect the final performance of the concrete, especially the long-term strength. This is because stone powder is an inert component and basically does not contribute to the later strength. Moreover, after adding stone powder, the stone powder is dispersed in the pores as a filler. The dispersion state of the stone powder changes during the freeze-thaw cycle, resulting in poor freeze-thaw cycle performance. Summary of the invention
[0006] In order to solve the existing technology. Specifically, the present invention provides the following technical solutions to solve the above technical problems: A concrete containing modified living fossil powder comprises the following raw materials in parts by mass: 200-300 parts of cement, 30-50 parts of fly ash, 30-50 parts of slag, 40-60 parts of modified granite powder, 30-40 parts of modified limestone powder, 5-10 parts of silicon powder, 600-800 parts of machine-made sand, 900-1300 parts of crushed stone, 15-25 parts of cross-linked polyurethane resin, 5-10 parts of water reducer, and 130-160 parts of water; the modified granite powder is prepared by modifying granite powder with a silane coupling agent; the modified limestone powder is prepared by first calcining limestone powder and then modifying it with an aluminate coupling agent and stearate; the cross-linked polyurethane resin is obtained by polycondensing diisocyanate, terminal hydroxyl silicone oil, small molecule diol and small molecule polyol.
[0007] Furthermore, the specific surface area of granite powder and limestone powder is 300-350m 2 / kg.
[0008] Furthermore, in the preparation of the modified granite powder, the silane coupling agent is selected from at least one of an aminosilane coupling agent and a mercaptosilane coupling agent; the amount of the silane coupling agent is 20-30wt% of the mass of the granite powder; further, the aminosilane coupling agent is selected from γ-aminopropyltrimethoxysilane (KH-540), 3-aminopropyltriethoxysilane (KH-550), N-2-aminoethyl-3-aminopropyltrimethoxysilane (KH- 792), γ-diethylenetriaminepropylmethyldimethoxysilane (Si-603), N-2-aminoethyl-3-aminopropylmethyldimethoxysilane (Si-602); the mercaptosilane coupling agent is selected from at least one of 3-mercaptopropyltriethoxysilane (KH-580), 3-mercaptopropyltrimethoxysilane (KH-590), and bis-[γ-(triethoxysilyl)propyl]tetrasulfide (Si-69).
[0009] Preferably, the silane coupling agent is a compound of an aminosilane coupling agent and a mercaptosilane coupling agent in a mass ratio of 1-5:1-5, and more preferably, the aminosilane coupling agent and the mercaptosilane coupling agent are compounded in a mass ratio of 1-2:1-2.
[0010] Furthermore, the modified granite powder is prepared by a preparation method comprising the following steps: Under ultrasonic conditions, granite powder is dispersed in an alcohol aqueous solution, a silane coupling agent is added, the temperature is raised for reaction, the mixture is filtered after cooling, washed with alcohol, and dried to obtain modified granite powder. The alcohol in the alcohol aqueous solution accounts for 40-60 vol%, and the alcohol is selected from at least one of methanol, ethanol, isopropanol, ethylene glycol, and propylene glycol. The temperature is raised to 30-40°C, and the reaction time is 4-6 hours.
[0011] Furthermore, in the preparation of modified limestone powder, the aluminate coupling agent is selected from at least one of isopropoxy distearate acyloxyaluminate, distearate isopropyl aluminate, triisopropoxy aluminum, and tri-n-butoxy aluminum; the stearate is selected from at least one of magnesium stearate, calcium stearate, sodium stearate, and potassium stearate. The mass ratio of limestone powder, aluminate coupling agent, and stearate is 100:25-40:6-10; calcination is performed at 700-900°C for 4-6h. After calcination, the high temperature destroys the crystal structure, improves the activity, and is conducive to subsequent modification. However, the calcination temperature needs to be controlled to avoid overburning.
[0012] Further, the modified limestone powder is prepared by a preparation method comprising the following steps: after the limestone powder is dried, it is added to a muffle furnace, calcined at 700-900° C. for 4-6 hours in an air atmosphere, ground after cooling, added to a high-speed kneader for stirring and preheating, an aluminate coupling agent and a stearate are added, and kneaded and mixed at high speed to obtain the modified limestone powder. The working parameters of the high-speed kneader are well known in the art, such as a rotation speed of 20-50 rpm, a pressure of 0.6-0.8 MPa, and an electric heating power of 5-15 kW.
[0013] The inventor unexpectedly found that when granite powder and limestone powder are modified, the granite powder is wet-modified with a silane coupling agent, and the limestone powder is dry-modified with an aluminate coupling agent and stearate. The two modified stone powders obtained by this specific modification method have the best matching effect and can obtain concrete with the best comprehensive performance. In the present invention, the stone powder not only fills the gaps between the materials and plays the role of filling the skeleton, but also the present invention adopts the matching effect of two different stone powders to induce cement hydration, so that the long-term strength of the cured concrete is also improved. Limestone powder also has a blocking effect on the conversion of calcium sulfide to monosulfide type, increasing stability. In addition, the composite modified stone powder can also inhibit the cracks generated during the freeze-thaw process, thereby improving the freeze-thaw resistance of concrete.
[0014] Furthermore, in the preparation of the cross-linked polyurethane resin, the molar ratio of diisocyanate, terminal hydroxyl silicone oil, small molecule diol and small molecule polyol is 1-1.2: 0.1-0.2: 0.8-0.9: 0.005-0.01; the diisocyanate is selected from at least one of isophorone diisocyanate, toluene-2,4-diisocyanate and dicyclohexylmethane diisocyanate; the number average molecular weight of the terminal hydroxyl silicone oil is 30000-50000, the small molecule diol is selected from C2-4 diol, preferably at least one of ethylene glycol, 1,3-propylene glycol and 1,4-butanediol; the small molecule polyol is selected from at least one of pentaerythritol, dipentaerythritol and trihydroxyaminomethane.
[0015] Further, the cross-linked polyurethane resin is prepared by a preparation method comprising the following steps: adding diisocyanate to a reaction container, adding terminal hydroxyl silicone oil, small molecule diol, and small molecule polyol under an inert atmosphere, mixing evenly, adding an organic tin catalyst, stirring and reacting at 20-40° C. for 4-6 hours until the NCO content no longer changes, cooling, and obtaining a cross-linked polyurethane resin. Further, the organic tin catalyst is selected from at least one of dioctyltin dilaurate, dibutyltin dilaurate, and dibutyltin diacetate, and the amount of the organic tin catalyst is 1-5% of the total mass of the monomers.
[0016] Furthermore, the cement is silicate cement with a strength of more than 42.5; the fly ash is grade II fly ash, and the slag powder is grade S95 fly ash; the particle size of the silica powder is 100-300nm; the crushed stone is 5-25mm continuously graded, and the machine-made sand has a fineness modulus of 2.2-3.1 and is grade II; the water reducer is a polycarboxylic acid water reducer, and the water reduction rate is 25-30%.
[0017] The present invention also provides a method for preparing the above-mentioned concrete containing modified activated fossil powder, comprising the following steps: (S1) crushed stone and machine-made sand are dry-mixed and then cement, fly ash, slag, silica powder, modified granite powder and modified limestone powder are added and mixed evenly to obtain a dry mix; (S2) mixing water, a water reducing agent, and a cross-linked polyurethane resin uniformly to obtain a dispersion; (S3) The dry mixed material and the dispersion liquid are mixed uniformly to obtain concrete.
[0018] There is no particular limitation on the method of mixing the materials evenly in steps (S1) and (S2), as long as the materials can be mixed sufficiently and evenly. For example, step (S1) uses a high-speed mixer, and step (S2) uses stirring, ultrasound, etc.
[0019] Furthermore, after the concrete is obtained, it is poured into a mold and cured to form the concrete. The curing conditions are 20-25° C. and a relative humidity of 85-95%.
[0020] The content of stone powder in the concrete of the present invention is relatively high, but it still has excellent workability and late strength, overcoming the defect that the content of stone powder in concrete cannot be too high otherwise it affects its performance. The increase in the content of stone powder can reduce the use of relatively high-priced fly ash and mineral powder, and reduce the cost of concrete. The present invention improves the defect of poor workability caused by high stone powder content by combining two modified stone powders and a cross-linked polyurethane polymer. The two modified stone powders have a synergistic effect, while improving the hydration activity of the stone powder, they will not excessively reduce the strength of the concrete after curing. The late strength of concrete mainly depends on the formation of hydrated calcium silicate and hydrated calcium aluminate. If the stone powder is not modified, it will not contribute to the late strength. The modified stone powder activated by two different modifiers of the present invention has a coordination effect, and combined with the cross-linked polyurethane resin, the interweaving of stone powder and hydration products is increased, so that the initial strength and late strength of the concrete, as well as the freeze-thaw resistance are improved at the same time, and the fluidity of the concrete is not adversely affected. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further explained below through specific embodiments.
[0022] The cement is P.O42.5 silicate cement, the stone powder is granite powder, the mineral powder is S95 grade mineral powder, the fly ash is grade II fly ash, the average particle size of the silica powder is 100nm, the crushed stone is 5-25mm continuous grading, the water reduction rate of the polycarboxylic acid water reducer is 28%, and the machine-made sand has a fineness modulus of 2.6 and is grade II.
[0023] Preparation Example 1-1 Under 100kHz ultrasonic conditions, 100 parts by mass of granite powder (BET = 320m 2 / kg) was dispersed in an ethanol aqueous solution (ethanol volume accounted for 50%), 20 parts by mass of a silane coupling agent was added, the silane coupling agent was a compound of KH-550 and KH-580 in a mass ratio of 1:1, the temperature was raised to 35°C for reaction for 5h, the mixture was cooled and filtered, washed with ethanol, and dried to obtain modified granite powder 1.
[0024] Preparation Example 1-2 The other conditions were the same as those in Preparation Example 1-2, except that the silane coupling agent was 20 parts by mass of KH-550, and modified granite powder 2 was obtained.
[0025] Preparation Example 1-3 The other conditions were the same as those in Preparation Example 1-2, except that the silane coupling agent was 20 parts by mass of KH-580, and modified granite powder 3 was obtained.
[0026] Comparative Preparation Example 1 100 parts by mass of granite powder (BET=320m 2 / kg) was added into a high-speed kneader and preheated to 70°C with stirring, 35 parts by mass of distearoyloxyisopropylaluminate and 8 parts by mass of magnesium stearate were added, and the mixture was stirred at high speed and mixed evenly to obtain modified granite powder 4.
[0027] Preparation Example 2-1 100 parts by mass of limestone powder (BET=330m 2 / kg) was dried, added into a muffle furnace, calcined at 750°C for 6h in an air atmosphere, cooled, ground, added into a high-speed kneader, stirred and preheated to 70°C, 35 parts by mass of distearyloxyisopropylaluminate and 8 parts by mass of magnesium stearate were added, and mixed evenly with high-speed stirring to obtain modified limestone powder 1.
[0028] Preparation Example 2-2 100 parts by mass of limestone powder (BET=330m 2 / kg) was dried, added into a muffle furnace, calcined at 750°C for 6h in an air atmosphere, cooled, ground, added into a high-speed kneader, stirred and preheated to 70°C, 25 parts by mass of triisopropoxyaluminum and 10 parts by mass of calcium stearate were added, and mixed uniformly by high-speed kneading to obtain modified limestone powder 2.
[0029] Comparative Preparation Example 2 100 parts by mass of limestone powder (BET=330m 2 / kg) was dispersed in an ethanol aqueous solution (ethanol volume accounted for 50%), 20 parts by mass of a silane coupling agent was added, the silane coupling agent was a compound of KH-550 and KH-580 in a mass ratio of 1:1, the temperature was raised to 35°C for reaction for 5h, the mixture was cooled and filtered, washed with ethanol, and dried to obtain modified limestone powder 3.
[0030] Preparation Example 3-1 Isophorone diisocyanate was added to the reaction container, and terminal hydroxyl silicone oil (number average molecular weight 42000), ethylene glycol and pentaerythritol were added under nitrogen atmosphere; the feeding ratio was controlled so that the molar ratio of isophorone diisocyanate, terminal hydroxyl silicone oil, ethylene glycol and pentaerythritol was 1.1:0.2:0.8:0.05, and the materials were stirred after feeding to mix them evenly, and a catalyst dioctyltin dilaurate was added in an amount of 2wt% of the total mass of the monomers, and the temperature was raised to 30°C and stirred for reaction for 5 hours until the NCO content no longer changed, and the temperature was lowered to obtain a cross-linked polyurethane resin 1.
[0031] Preparation Example 3-2 The other conditions were the same as those in Preparation Example 3-1, except that the monomer was a mixture of isophorone diisocyanate, terminal hydroxyl silicone oil, ethylene glycol, and trihydroxyaminomethane in a molar ratio of 1.1:0.1:0.9:0.1 to obtain a cross-linked polyurethane resin 2.
[0032] Comparative Preparation Example 3 Other conditions were the same as those in Preparation Example 3-1, except that pentaerythritol was not added to obtain a non-crosslinked polyurethane resin.
[0033] Example 1 (S1) 1053 parts by mass of crushed stone and 705 parts by mass of machine-made sand were dry-mixed, and then 246 parts by mass of cement, 40 parts by mass of Class II fly ash, 42 parts by mass of slag, 8 parts by mass of silicon powder, 50 parts by mass of modified granite powder 1 obtained in Preparation Example 1-1, and 36 parts by mass of modified limestone powder 1 obtained in Preparation Example 2-1 were mixed by a high-speed mixer to obtain a dry mix; (S2) Under ultrasonic conditions, 140 parts by mass of water, 6.8 parts by mass of polycarboxylic acid water reducer, and 21.4 parts by mass of the cross-linked polyurethane resin prepared in Preparation Example 3-1 were mixed uniformly to obtain a dispersion; (S3) The dry mix and the dispersion are mixed evenly to obtain concrete, which is poured into a mold and cured at 20-25° C. and 90-95 RH%.
[0034] Example 2 The other conditions are the same as those in Example 1, except that in step (S1), the modified limestone powder 1 obtained in Preparation Example 2-1 is replaced by the modified limestone powder 2 obtained in Preparation Example 2-2.
[0035] Example 3 The other conditions are the same as those in Example 1, except that in step (S1), the modified granite powder 1 obtained in Preparation Example 1-1 is replaced by an equal mass of modified granite powder 2 obtained in Preparation Example 1-2.
[0036] Example 4 The other conditions are the same as those in Example 1, except that in step (S1), the modified granite powder 1 obtained in Preparation Example 1-1 is replaced by an equal mass of modified granite powder 3 obtained in Preparation Example 1-3.
[0037] Example 5 The other conditions are the same as those in Example 1, except that in step (S2), the cross-linked polyurethane resin 1 prepared in Preparation Example 3-1 is replaced by an equal mass of the cross-linked polyurethane resin 2 prepared in Preparation Example 3-2.
[0038] Comparative Example 1 Other conditions are the same, except that in step (S1), the modified granite powder 1 obtained in Preparation Example 1-1 is replaced by the modified granite powder 4 of equal mass obtained in Comparative Preparation Example 1.
[0039] Comparative Example 2 Other conditions are the same, except that in step (S1), the modified limestone powder 1 obtained in Preparation Example 2-1 is replaced by the modified limestone powder 3 obtained in Comparative Preparation Example 2 of equal mass.
[0040] Comparative Example 3 Other conditions are the same, except that in step (S2), the cross-linked polyurethane resin 1 prepared in Preparation Example 3-1 is replaced by an equal mass of non-cross-linked polyurethane resin prepared in Comparative Preparation Example 3.
[0041] Comparative Example 4 Other conditions are the same, except that in step (S1), the modified granite powder 1 obtained in Preparation Example 1-1 is replaced by an equal mass of granite powder, and the modified limestone powder 1 obtained in Preparation Example 2-1 is replaced by an equal mass of limestone powder. That is, the granite powder and limestone powder are not modified.
[0042] Application Examples The concrete obtained in the above examples and comparative examples was cured and tested for performance. The compressive strength was tested according to the standard GB / T500812019, and the freeze-thaw cycle resistance was tested according to GB / T50085-2009. The number of freeze-thaw cycles corresponding to the occurrence of visible cracks on the test block was recorded. The results are shown in Table 1 below: Table 1 Concrete properties
[0043] From the data in Table 1, it can be seen that the present invention uses two kinds of stone powder with different chemical compositions, wherein the granite powder is modified by a silane coupling agent, and the limestone powder is modified by an aluminate coupling agent and a stearate, to obtain two kinds of modified stone powder, and then combined with a cross-linked polyurethane resin, a concrete with excellent comprehensive performance and high stone powder content can be prepared. If the modification method is changed, or there is no modification, or the polyurethane resin is not cross-linked, the purpose of the present invention cannot be achieved smoothly. It shows that the two kinds of modified stone powder and the cross-linked polyurethane resin can play a cooperative role and jointly improve the performance of concrete.
Claims
1. A concrete containing modified activated fossil powder, characterized in that: The invention comprises the following raw materials in parts by weight: 200-300 parts of cement, 30-50 parts of fly ash, 30-50 parts of slag, 40-60 parts of modified granite powder, 30-40 parts of modified limestone powder, 5-10 parts of silicon powder, 600-800 parts of machine-made sand, 900-1300 parts of crushed stone, 15-25 parts of cross-linked polyurethane resin, 5-10 parts of water reducer and 130-160 parts of water; the modified granite powder is prepared by modifying granite powder with a silane coupling agent; the modified limestone powder is prepared by first calcining limestone powder and then modifying it with an aluminate coupling agent and stearate; the cross-linked polyurethane resin is obtained by polycondensing diisocyanate, terminal hydroxyl silicone oil, small molecule diol and small molecule polyol.
2. The concrete containing modified activated rock powder according to claim 1, characterized in that: The specific surface area of granite powder and limestone powder is 300-350m 2 / kg.
3. The concrete containing modified activated rock powder according to claim 1, characterized in that: In the preparation of modified granite powder, the silane coupling agent is selected from at least one of aminosilane coupling agent and mercaptosilane coupling agent; the amount of silane coupling agent is 20-30wt% of the mass of granite powder.
4. The concrete containing modified activated rock powder according to claim 3, characterized in that: The aminosilane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, γ-diethylenetriaminepropylmethyldimethoxysilane, and N-2-aminoethyl-3-aminopropylmethyldimethoxysilane; the mercaptosilane coupling agent is selected from at least one of 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide.
5. The concrete containing modified activated rock powder according to claim 3, characterized in that: The silane coupling agent is a compound of an aminosilane coupling agent and a mercaptosilane coupling agent in a mass ratio of 1-2:1-2.
6. The concrete containing modified activated rock powder according to claim 1, characterized in that: In the preparation of modified limestone powder, the aluminate coupling agent is selected from at least one of isopropoxy distearate acyloxy aluminate, distearate isopropyl aluminate, triisopropoxy aluminum, and tri-n-butoxy aluminum; the stearate is selected from at least one of magnesium stearate, calcium stearate, sodium stearate, and potassium stearate; the mass ratio of limestone powder, aluminate coupling agent, and stearate is 100:25-40:6-10; and the calcination is performed at 700-900°C for 4-6h.
7. The concrete containing modified activated rock powder according to claim 1, characterized in that: In the preparation of the cross-linked polyurethane resin, the molar ratio of diisocyanate, terminal hydroxyl silicone oil, small molecule diol and small molecule polyol is 1-1.2: 0.1-0.2: 0.8-0.9: 0.005-0.01; the diisocyanate is selected from at least one of isophorone diisocyanate, toluene-2,4-diisocyanate and dicyclohexylmethane diisocyanate; the number average molecular weight of the terminal hydroxyl silicone oil is 30000-50000, the small molecule diol is selected from C2-4 diol; the small molecule polyol is selected from at least one of pentaerythritol, dipentaerythritol and trihydroxyaminomethane.
8. The concrete containing modified activated rock powder according to claim 7, characterized in that: The cross-linked polyurethane resin is prepared by a preparation method comprising the following steps: adding diisocyanate into a reaction container, adding terminal hydroxyl silicone oil, small molecule diol and small molecule polyol under an inert atmosphere, mixing uniformly, adding an organic tin catalyst, stirring and reacting at 20-40° C. for 4-6 hours until the NCO content no longer changes, cooling, and obtaining the cross-linked polyurethane resin.
9. The concrete containing modified activated rock powder according to claim 1, characterized in that: The cement is silicate cement with a strength of 42.5 or above; and / or The fly ash is Class II fly ash; and / or, The slag powder is S95 grade fly ash; and / or, The particle size of the silicon powder is 100-300 nm; and / or, The crushed stone is of continuous gradation of 5-25 mm; and / or, Machine-made sand with a fineness modulus of 2.2-3.1, Grade II; and / or, The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is 25-30%.
10. The method for preparing concrete containing modified activated fossil powder according to any one of claims 1 to 9, characterized in that: The following steps are involved: (S1) crushed stone and machine-made sand are dry-mixed, and then cement, fly ash, slag, silica powder, modified granite powder, and modified limestone powder are added and mixed evenly to obtain a dry mix; (S2) mixing water, a water reducing agent, and a cross-linked polyurethane resin uniformly to obtain a dispersion; (S3) The dry mix and the dispersion are mixed uniformly to obtain concrete.
Citation Information
Patent Citations
Modified limestone powder for preparing concrete
CN103524062A
Active stone powder for concrete and preparation method thereof
CN107986657A
Package-purposed plastic-based film containing itaconate
CN103044743A
Modified calcium oxide expansive agent used for cement concrete and preparation method thereof
CN104671700A
Fly ash modified ABS composite material and preparation method thereof
CN104845016A